The effect of labour hopscotch framework on maternal and neonatal outcomes in pregnant women: A randomized controlled trial. - Saeedeh Askari; Mina Iravani; Parvin Abedi; Bahman Cheraghian; Eesa Mohammadi; Shayesteh Jahanfar (PLoS ONE)
Trial registration ClinicalTrials.gov IRCT20161106030750N2.